EFFECTS OF POTASSIUM BROMATE ON THE KIDNEY AND HAEMATOLOGICAL PARAMETERS OF SWISS ALBINO MICE - STUTI, MARIA; D’SOUZA, DORIS (The Bioscan, 2013)
The present study aimed to investigate the possible effects of potassium bromate toxicity on histological, haematological and biochemical parameters in Swiss albino mice. Mice were orally administered with potassium bromate at the rate of 150 mg/kg body weight daily in a single dose for 30, 60 and 120 days. The chemical significantly reduced the RBC count (p<0.01) Hb% (p<0.01) and platelet count (p<0.01), while it increased significantly the urea (p<0.01) and creatinine level (p<0.01) and decreased total protein and Albumin (p<0.01) Histopathological examination showed degenerative changes of tubular cells, cytoplasma vacuolation, cellular infiltration, tubular dilation with eosinophilic debris and clear cell cytoplasm were observed. These findings suggest that KBrO3 affects the physiological and biochemical activities of Swiss albino mice.